Pertenencia territorial y presentaciones del conflicto social en la construcción cultural de una región: El Mante, Tamaulipas - Marielle Pepin Lehalleur (Estudios sobre las Culturas Contemporáneas)
The present text has the objective of presenting the network-based project of investigation that seeks to reflect on the uses and social appropriation of the soap opera (telenovela) in Mexico. It takes as its point of reference the telenovela Mirada de Mujer, produced by Television Azteca. It is concerned with understanding how telenovelas construct their relationship with Mexican publics, what type of television culture that has been constituted through this relation; at the same time it seeks to reflect upon the regional behavior of the participating cities. This project has been constructed on the basis of the configuration of the National Network of Research of the Programa Cultura of the University of Colima. There as six participating universities: Universidad de Colima, Universidad Iberoamericana (Leon and Tijuana campuses), Universidad Autonoma de San Luis Potosi and Universidad Intercontinental of Mexico Cit´.